Academic Anxiety sebagai Distorsi Kognitif terhadap Skripsi: Penerapan Konseling Cognitive Behavior Therapy dengan Musik - Situmorang, Dominikus David Biondi (Program Studi bimbingan Konseling PPs UNM Makassar, 2018)
In Indonesia, undergraduate thesis is still a pretty scary end task for most students. Many of them do procrastination, keep away from supervisors, do non-productive things as a form of anxiety diversion, and the most extreme is to commit suicide as a result of excessive academic anxiety on undergraduate thesis. The education counselor as one of the college internal agents is expected to solve the problems that often occur every year. Based on Cognitive Behavior Therapy (CBT) counseling approach, the academic anxiety experienced by students is a cognitive distortion caused by maladaptive core beliefs. The process to change the student's core beliefs to be more adaptive can be done with a modern technique, that is through music. In its application, CBT counseling using integrative technique through music consists of two, passive and active music therapy. What we need to know more about how CBT views academic anxiety as a problem and how the way to use integrative technique through music, so that counselors in Indonesia can comprehend conceptually about CBT counseling intervention with music appropriately in the future, in order to help students free from academic anxiety towards undergraduate thesis.